Report on a complete chloroplast genome sequence of wild apple tree, Malus sieversii (Lebed.) M. Roem. Issue 2 (2nd April 2020) - Ha, Young-Ho; Maisupova, Bagila; Choi, Kyung; Kim, Hyun-Jun; Dosmanvetov, Daniyar; Mambetov, Bulkair; Utebekova, Ainur; Kim, Dong-Kap; Chang, Kae Sun; Kim, Aleksey; Lee, Soo-Rang; Oh, Seung Hwan
Abstract: We report a complete chloroplast genome sequence of Malus sieversii . The CP genome was 160, 223 bp in length with a typical quadripartite structure. Length of large single-copy (LSC) was 88, 334 bp, whereas small single-copy (SSC) was 19, 179 bp in length. A pair of inverted repeats (IR) were 26, 355 bp. In total, 128 genes were found including 83 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The phylogenetic analysis on concatenated data set retrieved from 78 protein-coding genes revealed that M. sieversii was closely related with both M. × domestica and M. sylvestris.